2008
DOI: 10.1097/tp.0b013e318186d87b
|View full text |Cite
|
Sign up to set email alerts
|

“Natural” Human Leukocyte Antigen Antibodies Found in Nonalloimmunized Healthy Males

Abstract: Normal males were found to have HLA antibodies to infrequent HLA specificities. It is likely that these HLA antibodies are produced to cross-reactive epitopes found in microorganisms, ingested proteins and allergens-making them natural antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
5
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 282 publications
(265 citation statements)
references
References 16 publications
12
242
5
6
Order By: Relevance
“…The Cw* reactivity of IVIg is comparable to the high incidence of HLA-Ia reactivities found in normal sera. 11 IVIg reacted with several B* alleles, and high reactivity was observed with B*8201, B*1512, and B*4501. The high reactivity of IVIg observed with several B* alleles is also comparable to the incidence of HLA-B reactivity of normal nonalloimmunized male sera.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cw* reactivity of IVIg is comparable to the high incidence of HLA-Ia reactivities found in normal sera. 11 IVIg reacted with several B* alleles, and high reactivity was observed with B*8201, B*1512, and B*4501. The high reactivity of IVIg observed with several B* alleles is also comparable to the incidence of HLA-B reactivity of normal nonalloimmunized male sera.…”
Section: Resultsmentioning
confidence: 99%
“…The high reactivity of IVIg observed with several B* alleles is also comparable to the incidence of HLA-B reactivity of normal nonalloimmunized male sera. 11 IVIg also reacted strongly with a few A* alleles, including A*8001, A*3401, A*4301, A*6601, and A*6602. Interestingly, the high reactivity of IVIg with these A* alleles is strikingly similar to the high incidence of HLA-A reactivity observed with normal male sera.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other patients that were newly screen positive displayed nonspecific reactivity but no clear specificity pattern. Nonspecific reactivity can be found commonly in the healthy population (25). In transplantation, one study showed that de novo DSA was seen in up to 15% of kidney transplant patients followed over a mean of 4.6 years (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that this sensitive assay employing recombinant HLA antigens can result in a frequent detection of antibodies directed against a limited number of rare HLA antigens in nontransfused males and even in cord blood. 15,16 These antibodies have been termed 'natural antibodies', and the majority of targeted epitopes consist of hidden amino acids that are believed to be inaccessible in the intact form of the HLA antigens. 16 Indeed, natural antibodies detected in renal allograft recipients were not predictive of graft failure.…”
Section: Definitionsmentioning
confidence: 99%